Impact of Service Value to the Customer Retention of Selected Milk Tea Shops Along Valenzuela City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The increasing competition in the milk tea business has many factors to consider, especially inproviding a service specifically to the price and quality of milk tea products; the consumers areafter the prices offered by the different milk tea shops and also with the marketing strategythey impose for every product they launch. The purpose of the study is to determine theimpact of service value on the customer retention of selected Milk Tea shops alongValenzuela City in terms of age, gender, and socio-economic status.The result of the study revealed that the impact of service value on customer retention in milktea shops is “strongly agree” in terms of reliability, assurance, tangibles, empathy, andresponsiveness. However, the biggest problems encountered by the customers of milk teashops for service that they experience are long wait times and broken promises. Furthermore,there is no significant relationship between the service value effect and demographic profile.Overall, the study recommends that Milk Tea Shop should improve their service in terms ofproviding fast service to the customer; they should conduct an evaluation from customers’feedback at least once a month to decide what kind of action are they going to perform; theymust always be conscious regarding to the quality of their products and equipment; and musthave physical store that can give comfortable waiting area to the customers.
Keywords: Business